2021
DOI: 10.3390/plants10020216
|View full text |Cite
|
Sign up to set email alerts
|

Plants of the Spontaneous Flora with Beneficial Action in the Management of Diabetes, Hepatic Disorders, and Cardiovascular Disease

Abstract: The current pharmacological agents advised for the management of diabetes as well as cardiovascular and hepatic diseases are subject to numerous studies for safety and efficacy. Therefore, it is worth looking into alternative therapeutic aids such as natural products of medicinal plants. By a broad review of in vitro and in vivo studies on the various dandelion, chicory, and mulberry extracts, this work highlights their bioactive compounds and therapeutic action when used as a prevention and management aid in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 140 publications
(78 reference statements)
0
9
0
Order By: Relevance
“…Despite that, there is an ongoing effort to find out more effective and affordable antidiabetic drugs, with less side effects (American Diabetes Association 2020 ; Knura et al 2021 ). Taking advantage of the ethnopharmacological uses, plants have been selected for bioassay-guided isolation and identification of new lead antidiabetic compounds (Barzkar et al 2020 ; Gaonkar and Hullatti 2020 ; Fu et al 2021 ; Wasana et al 2021 ; Lee et al 2021 ; Ignat et al 2021 ; Abu-Odeh and Talib 2021 ). Thus, metformin, the drug mostly prescribed on the treatment of type-2 diabetes, is a synthetic derivative of galegine, isolated from Galega officinalis L. (Fabaceae) (Cragg and Newman 2013 ; Bailey 2017 ).…”
Section: Antidiabetic Activitymentioning
confidence: 99%
“…Despite that, there is an ongoing effort to find out more effective and affordable antidiabetic drugs, with less side effects (American Diabetes Association 2020 ; Knura et al 2021 ). Taking advantage of the ethnopharmacological uses, plants have been selected for bioassay-guided isolation and identification of new lead antidiabetic compounds (Barzkar et al 2020 ; Gaonkar and Hullatti 2020 ; Fu et al 2021 ; Wasana et al 2021 ; Lee et al 2021 ; Ignat et al 2021 ; Abu-Odeh and Talib 2021 ). Thus, metformin, the drug mostly prescribed on the treatment of type-2 diabetes, is a synthetic derivative of galegine, isolated from Galega officinalis L. (Fabaceae) (Cragg and Newman 2013 ; Bailey 2017 ).…”
Section: Antidiabetic Activitymentioning
confidence: 99%
“…Other studies have confirmed that polyphenols in dandelion leaf and stem extracts are useful in the treatment of type 2 diabetes and obesity. An ethanolic extract of dandelion was proved to inhibit the formation of advanced glycation end products at IC50 = 69.4 mg/L compared to the antiglycation drug-aminoguanidine (IC50 = 138 mg/L) [ 54 ]. Dandelion components also show activity in regulating the pathways responsible for insulin release, most likely by inhibiting certain enzymes involved directly and indirectly in carbohydrate breakdown in the Krebs cycle and glycolytic cycle.…”
Section: Pharmacological Activity Of Dandelion For Potential Use In T...mentioning
confidence: 99%
“…In addition to its flavor qualities, dandelion is traditionally used in infusions and decoctions as aperitif, tonic, and stimulant; however, studies suggest only a minor effect [ 17 ]. It has also been used for many centuries as a remedy for kidney, liver, and gallbladder disorders [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. The beneficial effects of dandelion are dependent on the chemical compounds contained in the plant.…”
Section: General Description Of Dandelion and Its Productsmentioning
confidence: 99%